2018
DOI: 10.1155/2018/5307106
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and AFM Characterization of G-Quadruplex Electrochemical Biosensors and Applications

Abstract: Guanine-rich DNA sequences are able to form G-quadruplexes, being involved in important biological processes and representing smart self-assembling nanomaterials that are increasingly used in DNA nanotechnology and biosensor technology. G-quadruplex electrochemical biosensors have received particular attention, since the electrochemical response is particularly sensitive to the DNA structural changes from single-stranded, double-stranded, or hairpin into a G-quadruplex configuration. Furthermore, the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 138 publications
0
25
0
Order By: Relevance
“…To a large extent, the structure of G‐quadruplex nucleic acid has high thermodynamic stability under close physiological conditions. [ 126–129 ] Biffi et al. reported that G‐quadruplex nucleic acid can be engineered to produce and apply structure‐specific antibodies, which can quantitatively deliver the structure of DNA G‐quadruplex in human cells.…”
Section: Smfs Study On Intra‐ or Intermolecular Interactionsmentioning
confidence: 99%
“…To a large extent, the structure of G‐quadruplex nucleic acid has high thermodynamic stability under close physiological conditions. [ 126–129 ] Biffi et al. reported that G‐quadruplex nucleic acid can be engineered to produce and apply structure‐specific antibodies, which can quantitatively deliver the structure of DNA G‐quadruplex in human cells.…”
Section: Smfs Study On Intra‐ or Intermolecular Interactionsmentioning
confidence: 99%
“…[18a], Notably, hemin binding for generation of DNAzymes with peroxidase‐like activity and for the development of molecular sensing devices has found widespread attention and has been discussed in several reviews , ,. [86a], Herein, we will focus on the use of PPIX and its Zn(II) complex in conjunction with G‐quadruplex structures as biosensors.…”
Section: Ppix Derivatives For Chemical Biology Applicationsmentioning
confidence: 99%
“…The electrostatic attractive force between the bimetallic NPs and GCE aided the uniform deposition of NPs. More details of the Pb 2+ -aptamer interaction can be found elsewhere [40][41][42][43][44][45].…”
Section: Molecular Mechanism Of the Modified Electrode Actionmentioning
confidence: 99%